Travel Data Sequence from Multi-Source Recommendation System - Shobarani, Ms.; Anandam Velagandula, Dr.; Ravula Arun Kumar, Mr.; Anandkumar, B (International Journal of Engineering and Technology, 2018)
Due to different sort of preferences and restrictions of a trip such as time source limitation and every tourist’s destination points the travel based recommendation has become a challenging task. Most importantly the data generated by the geo-tagged social channel from the geo based tag tweets, snapshots of credentials.  Due to examining this, extended data allows us to invent the profiles, daily mobility patterns, and results of the user’s. To resolve the issues and challenges of capacity providing their personalized and sequential travel to make package recommendation to a topical package model and to take using social media info in which mechanically mine person travel interest with another quality like time, cost, and period of wayfaring. Here, we had a proposal that a travel data sequence after a multi source recommendation system. We implemented a location recommendation system that derives personal preferences while accounting for restraints irremissibly by road capacity in order to change the demand of travel. We first infer unobserved preferences using a machine learning technique from data mining records. It extends our method to provide personalized suggestions based on user geo co-ordinates points. By utilizing the tree based hierarchal graphs (TBHG), location histories of the multiple users’ have been modeled.  In order to collect the selected places interest level and travel knowledge of user’s, the HITS model had developed based on TBHG. Finally, hybrid filtering approach based on HITS is utilized to get the global positioning system (GPS) based personalized recommendation system. And for image based search similar images with the tag information are retrieved for the query image users.